Magnetic data of profile MSM122_P05-1 over the Oceanographer transform fault, North Atlantic, of MARIA S. MERIAN cruise MSM122 - Ingo Grevemeyer; Lars H Rüpke; Jérôme Dyment; Christian Hübscher (PANGAEA, 2025)
During the cruise MSM122 of the German research vessel MARIA S. MERIAN, we recorded densely spaced magnetic field measurement over the Oceanographer and Hayes transform faults in the North Atlantic to the Southwest of the Azores and hence at segment boundries offseting the Mid-Atlantic Ridge. Additional data were recorded to the south of Hayes transform and on the transits to Halifax outside of any territorial water. The total magnetic field was measured using two SeaSpy magnetometers which were towed at 350 m and 450 m, respectively, behind the stern of the ship, sampling the data continuously every 2 seconds. The ships navigation was corrected to match the position of the first magnetic sensor at 350 m behind the vessel. Uncorrected total field magnetic data are available in text/ascii format.